Pembelajaran Kewirausahaan Dan Lingkungan Keluarga Kaitannya Dengan Intensi Berwirausaha Siswa SMK - Hermayanti, Mega; Mulyadi, Hari (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
This study was conducted to see how much influence entrepreneurial learning and family environment to the entrepreneurial intention of students. Type of research is descriptive and verification with samples taken as many as 108 respondents from 151 population. Data analysis techniques in this study using multiple linear regression. Based on the results of research using multiple linear regression analysis, showed that entrepreneurial learning and family environment significantly affect the entrepreneurial intention ofÂ  students. The difference in this study with other studies located from the object of research, measurement instruments used, population and sample, as well as research results. In this study, using the theory of journals and books, so the theory used is different.